Release of DNA from cryogel PVA-DNA membranes (eXPRESS Polymer Letters, 2010)
Poly(vinyl alcohol) (PVA) hydrogels have been used for numerous biomedical and pharmaceutical applications, as a consequence of their non-toxic, non-carcinogenic and bioadhesive properties. In this communication the effect of different factors, such as type of electrolyte, ionic strength, temperature (ranging from 20 to 40°C) and cationic surfactants on the distribution coefficients (α) and release rate constants (kR) of deoxyribonucleic acid (DNA) from PVA-DNA blend gel matrices (of a sheet shape), will be presented and discussed. The release kinetic constant and the distribution coefficient of DNA are quite sensitive to the surrounding matrix media (e.g., kR ranges from 1.5•10–8 to 4.7•10–7 s–1). The analysis of the temperature dependence on kR shows that the activation energy for the DNA desorption to an aqueous solution is equal to 21.2 kJ/mol. These results constitute a step forward towards the design of controlled DNA release PVA-based devices.